Analysis Of The Influence Of Leadership Style, Work Environment, And Motivation On Employee Performance In The Marketing Division At PT Ingco Teknika Indonesia - Bella Cyintia Maramis; Muhammad Yalzamul Insan; Kholilul Kholik (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of Leadership Style, Work Environment, and Motivation on Employee Performance in the Marketing Sector at PT. Ingco Teknika Indonesia. This study uses a quantitative method involving 40 employees as respondents. Data collection was carried out using questionnaires. The data obtained were analyzed using statistical formulas, namely by using the normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis with the SPSS Version 23.0 program. The results of this study indicate that leadership style has a positive and significant influence partially on performance.This can be seen from the t-value of 4.947 which is greater than the t-table of 2.02 with a significance level of 0.000, thus, H1 is accepted and H0 is rejected. The work environment has a positive and partially significant influence on performance. This can be seen from the t-value of 3.523 which is greater than the t-table of 2.02 with a significance level of 0.001, thus, H2 is accepted and H0 is rejected. Motivation has a positive and partially insignificant influence on performance. This can be seen from the t-value of 0,283 which is smaller than the t-table of 2.02 with a significance level of 0.779, thus, H3 is rejected and H0 is accepted. Leadership style, work environment and motivation have a significant influence simultaneously on performance. This can be seen from the F-value of 100.530 with a significance level of 0.000, thus, H4 is accepted and H0 is rejected.